Intra-cycle variation of the uterine cavity indentation assessed with three-dimensional ultrasound in natural and stimulated cycles. Issue 5 (May 2016) - Saravelos, Sotirios H.; Li, Tin-Chiu
Abstract: The recent ESHRE-ESGE classification for female genital anomalies attempts to promote objectivity in diagnosis of normal and septate uteri. The aim of this study was to ascertain whether the uterine cavity indentation – the characteristic feature of septate uteri – varies significantly throughout the cycle. Seventy consecutive women underwent three-dimensional ultrasound twice: 35 during the proliferative and luteal phase of a natural cycle, and 35 during the first and final day of a stimulated cycle. Endometrial thickness, interostial distance, cavity indentation and percentage of cavity indentation were all assessed in accordance with the ESHRE-ESGE consensus on diagnosis of female genital anomalies. Overall, throughout both cycles, there was a significant increase in endometrial thickness (from 4.6 mm to 10.2 mm; P < 0.001) and interostial distance (from 30.1 mm to 35.1 mm; P < 0.001), which was associated with a significant reduction in the percentage of cavity indentation (from 30.3% to 15.0%; P < 0.001). Between the first and second assessment, 3/70 (4.3%) patients had a change in diagnosis from septate to normal uterus, although this did not reach statistical significance. This observation of a significant intra-cycle variation of the uterine cavity indentation has important implications for both clinical practice and research.